If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -2 + -2t + 7 = 0 Reorder the terms: -2 + 7 + 4t + -2t = 0 Combine like terms: -2 + 7 = 5 5 + 4t + -2t = 0 Combine like terms: 4t + -2t = 2t 5 + 2t = 0 Solving 5 + 2t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2t = 0 + -5 2t = 0 + -5 Combine like terms: 0 + -5 = -5 2t = -5 Divide each side by '2'. t = -2.5 Simplifying t = -2.5
| tsquared-3t=28 | | 6b+15=0 | | -log(x)=9.87 | | X+11.7=20.93 | | 8-8=17x+5x | | (7x+2)=(2x-7) | | y(5y+7)(7y+6)=0 | | N/20=2/32 | | log[5](x-4)=1-log[5](x-8) | | 7(5t-4)-(2t+15t)=60 | | 0.7x+0.3=3.1 | | 67-2x=180 | | -4.2=-0.9u+0.3u | | x^0=12 | | 2(4)+3(-1)=11 | | -1.4x-5=2 | | 19x+14=(9x+2)*2 | | 3x/5=2/3 | | 22-4x=3x+78 | | -8/9x=-32/45 | | 19x+14=(2x+2)*2 | | 16t^2+32t+6=h | | (19x+14)=(2x+2)*2 | | 5x+2*8y=200 | | 180=2x+20 | | 3/2t=-2/3 | | 6n-4=142 | | 2x-5=x/3 | | 2(1)+3(3)=11 | | -18-6k=6(1+2x) | | 9y=-4x+27 | | 2.2/n=1.3/15 |